PENGELOLAAN KAS KECIL PADA PT PLN (Persero) UNIT PENDIDIKAN DAN PELATIHAN PALEMBANG - Aladin Aladin; Febriani Febriani; Mardiana Mardiana (EKSISTANSI, 2021)
Petty cash is used to finance the company's operational activities, which are routine in nature and relatively small in value, and cannot be processed through a contract mechanism. The focus of the discussion in this research is the documents and recording procedures used in petty cash management at PT PLN (Persero) Palembang Education and Training Unit. Petty cash management at PT PLN (Persero) UPDL Palembang is quite good. The use of little cash funds has also been categorized according to the type of expenditure and the number of funds used. After handing over the money from the petty cash holder to the user, it is necessary to provide a receipt/verification document signed by both parties to avoid mistakes.